2011
DOI: 10.1089/vbz.2010.0007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Individual Factors Associated with Hantavirus Infection in Bank Voles During an Epizootic: Implications for Puumala Virus Transmission Dynamics

Abstract: Puumala virus (PUUV), the causal agent of nephropathia epidemica in humans, is one of the many hantaviruses included in the list of emerging pathogens. Hantavirus infection is not distributed evenly among PUUV reservoir hosts (i.e., bank voles [Myodes glareolus]). Besides environmental factors and local population features, individual characteristics play an important role in vole PUUV infection risk. Identifying the relative importance of these individual characteristics can provide crucial information on PUU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…This result is consistent with other studies where hantavirus prevalence was negatively correlated with diversity [53][55], presence [56], or proportion [19], [57] (but see [52]) of non-host small mammals. However, we observed that an increasing number of non-host small mammals reduced the likelihood of a bank vole being infected when host density was constant (Table 2, Figure 3C).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with other studies where hantavirus prevalence was negatively correlated with diversity [53][55], presence [56], or proportion [19], [57] (but see [52]) of non-host small mammals. However, we observed that an increasing number of non-host small mammals reduced the likelihood of a bank vole being infected when host density was constant (Table 2, Figure 3C).…”
Section: Discussionsupporting
confidence: 93%
“…This result implies that transmission increases with bank vole density, either between infected and susceptible individuals or between susceptible individuals and an infectious environment. Several studies focusing on the PUUV hantavirus and bank voles have addressed the association between infection prevalence and host density [12], [19], [22], [37], [38], [51], [52], but positive relationships have only been found occasionally, and in most cases without time lags [12], [22], [52].…”
Section: Discussionmentioning
confidence: 99%
“…Although we are not aware of any studies which have examined this hypothesis directly, higher infection rates have been seen in old, breeding males (e.g. Tersago et al 2011), a pattern that would be predicted in species with male territorial dominance and associated high rates of scent marking and investigation. Continued, deliberate exposure to infected social signals may therefore be another factor behind the male-biased parasitism seen in some species (e.g.…”
Section: Box 4 Parallels Between Predation Risk and Infection Riskmentioning
confidence: 97%
“…The main host of PUUV is the bank vole (Myodes glareolus), and the virus is predominantly transmitted horizontally to humans via exposure to contaminated vole excreta [13,39,42]. Human infection is characterized by sudden onset of fever, head and backache, vomiting, and abdominal pain often accompanied by visual disturbances [24].…”
Section: Introductionmentioning
confidence: 99%